2012
DOI: 10.1002/14651858.cd003306.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Urinary diversion and bladder reconstruction/replacement using intestinal segments for intractable incontinence or following cystectomy

Abstract: , S. M. (2012). Urinary diversion and bladder reconstruction/replacement using intestinal segments for intractable incontinence or following cystectomy. Cochrane Database of Systematic Reviews, (2),-. [CD003306].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 42 publications
(4 reference statements)
1
40
0
1
Order By: Relevance
“…Without an established health related quality of life benefit,[28] and low performance rates in our own and other population based studies,[29] receipt of continent diversion as a quality indicator is controversial and will unlikely reach consensus among experts. One could argue that, if possible to ascertain, a more appropriate process measure would be documentation of an informed discussion regarding the risks and benefits of continent diversion for a patient without contraindication.…”
Section: Discussionmentioning
confidence: 99%
“…Without an established health related quality of life benefit,[28] and low performance rates in our own and other population based studies,[29] receipt of continent diversion as a quality indicator is controversial and will unlikely reach consensus among experts. One could argue that, if possible to ascertain, a more appropriate process measure would be documentation of an informed discussion regarding the risks and benefits of continent diversion for a patient without contraindication.…”
Section: Discussionmentioning
confidence: 99%
“…6,11 However, as survival after treatment for bladder disorders steadily improves and the number of patients with continent urinary diversion increases, this issue may assume greater importance. 1,20,22 Disorders of Hepatic Metabolism When intestine is used in urinary diversion, absorption of ammonia into the portal circulation increases because of the increased load of ammonia from the urine. 6,11,23 Under normal circumstance, the liver clears the increased ammonia load without significant alteration in serum ammonia levels.…”
Section: Bone Demineralizationmentioning
confidence: 99%
“…In adults, oncologic indications for removal of the bladder include both muscle invasive bladder cancer and recurrent nonmuscle invasive bladder cancer refractory to conservative treatment. 1 Children may also need radical cystectomy for malignancies, such as rhabdomyosarcoma. In addition, other nononcologic causes may occasionally result in the removal of the bladder and, consequently, a urinary diversion, such as severe neuropathic bladder, treatment refractory overactive bladder, interstitial cystitis, radiation cystitis, and tuberculosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, numerous studies, including a Cochrane review, have reported on the comparison of conduits and neobladders, with no definite unanimous superiority of one over the other [1219]. However, these studies were on ORC with no comparison of LRC conduit and neobladders found in the literature.…”
Section: Introductionmentioning
confidence: 99%